A fuzzy similarity measure based on equivalence relation with application in cluster analysis. Issue 3 (3rd July 2017) - Beg, Ismat; Rashid, Tabasam
Abstract: We propose a novel notion of fuzzy similarity measure between fuzzy sets by using fuzzy equivalence. Furthermore, a similarity base fuzzy relational clustering algorithm is formulated. Applications are given to illustrate the usefulness of the chosen fuzzy equivalence and similarity measure in a partition algorithm.